Hemato -biochemical changes in a Babesia gibsoni infected German sheperd dog-A case report - P.I.Ganesan; Chintada Archana; Nanda Shweta (The Indian Veterinary Journal, 2026)
A four years old German Sphered dog admitted in a private clinic, in Paralakhemundi, Gajapati district, Odisha state, India. With the clinical sign of hemoglobinuria, microscopic examination of the blood smear revealed the infection towards Babesia gibsoni. The hematological studies revealed decreased levels in hemoglobin, total leucocyte count, platelet count (PLT), hematocrit value (HCT) and the RBC count, followed by neutrophilia and lymphopenia. The biochemical studies showed, elevated bilirubin, SGOT/ AST, SGPT/ALT, alkaline phosphatase, CGT, total protein, globulin and A/G ratio. The serum creatinine level remained normal. The dog suffered with hemoglobinuria for 3 days and then brought to the clinic. The dog was resorted to the treatment with imidocarb on that day immediately but without success. The death of the dog occurred within 4 days after hemoglobinuria symptoms in the absence of immediate treatment and it was attributed to severe toxicity due to accumulation of heme in the kidney parenchyma and the development of glomerulonephritis by immune -mediated proteinuria